Organizations, humanism and AI : an aesthetics approach - Szostak, Micha?? (Routledge, 2026)
This volume explores the role of the aesthetics of the synergy between humanism and artificial intelligence (AI) on the level of institutions and organisations, influencing individuals' well-being. Grounded in the principles of the humanistic management paradigm-emphasising sustainability, social organisations and entrepreneurship, conscious capitalism, and the protection of human dignity-it investigates how aesthetic principles (harmony, transparency, emotional resonance, cultural adaptability, or depth insights), applied between a human-centric approach and the use of AI-powered solutions, may help shape public perceptions, foster trust, and affect the quality of institutions within politics, governance, media, and social services. An aesthetic perspective becomes crucial as AI's influence expands, shaping governance mechanisms, media, social interactions, and societal organisation. It enables a critical examination of the challenges, risks, and opportunities arising from this growing role, ensuring a responsible, conscious, and balanced approach to AI's integration into public life. Through theoretical insights, conceptual frameworks, practical case studies, and empirical investigations, it highlights the transformative potential of aesthetics. This book follows a progressive analytical approach, beginning with macro-level institutional frameworks (politics and governance), moving through public discourse (media and perception), and concluding with micro-level applications (social care and well-being). This structured narrative presents a coherent examination of key aspects demonstrating how aesthetic considerations influence the synthesis between the humanistic approach and AI in different domains of societal life.
Keywords: Humanism.; Artificial intelligence -- Social aspects.; Human body -- Technological innovations.; elektronické knihy; electronic books